Estratégias disciplinares em acolhimento residencial: um estudo com multi-informantes - Katarina Gueiros Hernandez (2021)
In Portugal, in 2019, 7046 children/adolescents were placed in institutions. Evidence on disciplinary strategies (DS) used in these contexts is sparse. This study aims at analysing the DS used by caregivers in residential care homes, based on multiple informants' reports - children/adolescents in care, caregivers and directors. It follows a theoretical framework that includes and relates the concept of quality in residential care, positive discipline and children's rights. A total of 424 children/adolescents, 266 caregivers and 60 directors in 60 residential care centres participated in this study. Data on DS were collected using the ARQUA-P system and analised using a mixed methodology. Qualitative content analysis allowed for the identification of 33 subcategories, organized into six categories, which were computed into three major types of DS: Positive and Induction-Based Strategies, Punitive Strategies and Strategies that Violate the Child's Rights. Additionally, a cluster analysis allowed for the identification of three groups of residential care centres that used different DS -Punitive Centres, Inductive Centres and Centres that violate the Child's Rights-, according to the perspective of the three informants. The results revealed significant differences between the three groups, according to the DS quality assessed by the investigators. There were no significant differences or associations between the clusters and the characteristics of caregivers (specific training and professional experience) and the residential care centres (typology, external supervision and caregivers' recruitment process). Implications for qualified practice in residential care were drawn from findings.